Hambatan pemberian ASI ekslusif pada ibu bekerja: teori ekologi sosial - Rakhmawati Agustina; Yayi Suryo Prabandari; Toto Sudargo (Jurnal Gizi Klinik Indonesia, 2020)
Obstacles of providing exclusive breastfeeding among working mothers using social-ecological theoryBackground: The coverage of exclusive breastfeeding (EBF) in Indonesia was increased to 38% but it was lower than the Millennium Development Goals (MDGs) target (80%). One of the influence factors is to return to work. Society assumed that a mother who stays at home more successful to provide EBF than working mothers. A previous study indicated that some obstacles become early cessation factors among working mothers.Objective: To explore the obstacle of breastfeeding using social-ecological theory.Methods: Qualitative research inquiry based on phenomenology design. Informants were chosen through purposive sampling. Inclusion criteria were working mothers who succeeded provide exclusive breastfeeding, had children age 6-24 months, lived, and formally worked at Manado. Data triangulation was conducted through in-depth interviews with the manager/supervisor/colleague. Data collected using in-depth interviews and observation.Results: A total of twelve informants have interviewed consists of six working mothers and six triangulation informants. The result indicated that lack of confidence was related to providing exclusive breastfeeding. This is caused by family influence, culture, health provider, and lack of awareness from the working place. A support group was the main factors that influence the mother to overcome all obstacles.Conclusions: The main obstacles for working mothers to provide EBF come from interpersonal factors that determined by other factors: intrapersonal, organizational, community. Therefore working mothers need breastfeeding preparation since early pregnancy to decrease breastfeeding obstacles.